The Place of the Association of Insurance and Reinsurance in the Warta SA Property Insurance Market - Gwizdała, Jerzy P. (Studia Oeconomica Posnaniensia, 2026)
The activity of the Warta Group SA has greatly contributed to the development of the insurance market in Poland. It introduced a number of solutions and applications for various classes of insurance offered to companies which have become the standard in the market. After more than 90 years in the business Warta has become one of the greatest players in the field of property insurance in Poland. Since its inception it has undergone the transformation of the economic system with positive results. This demonstrates the ability of its directors and the establishment of a product offering tailored to the needs of the property insurance market.